Lympa ngiectasia of the vulva accompanying congenital lymphedema - Okur, M Ihsan; Köse, Rüştü; Yildirim, A Mustafa; Çobano?lu, Bengü (Dermatology Online Journal, 2009)
Lymphangiectasia is a benign condition with multiple dilated lymph vessels in the dermis. Vulvar localization is rare and mostly depends on disturbing the lymphatic flow. We present a patient with vulvar lesions and ipsilateral congenital lower extremity lymphedema. Surgical excision eliminated the lymphangiectasia and improved the appearance of the edematous vulva. © 2009 Dermatology Online Journal.
Keywords: antibiotic agent; adult; article; case report; compression garment; dermis; endothelium; excision; female; general anesthesia; hereditary lymphedema; histopathology; human; human tissue; leg; lymphangiectasis; papule; scar; suture; vaginitis; vulva lymphangiectasia; wound healing